Speaking Anxiety in English Learning in Grade XI Students of Walisongo Pecangaan High School: Forms, Factors, and Strategies to Overcome It - Sulaiman, Raehani; Candraloka, Olyvia Revalita (Universitas Muhammadiyah Mataram, 2025)
This study maps the forms, factors, and strategies for overcoming speech anxiety in grade XI students at Walisongo Pecangaan High School (pesantren context). Using a descriptive qualitative approach (case study), six students were selected on a purposive–maximum variation basis. Data were collected through semi-structured interviews and class observations in speaking sessions, then analyzed thematically by triangulating cognitive, physiological, and behavioral indicators. The results showed that the majority of the speakers were at medium to high levels. Four forms of anxiety arise and intertwine: (1) physiological—cold sweats, tension, speech blocking; (2) cognitive—a sense of